Polymeric membrane fabrication for biomedical applications - Koh, Louisa Fei Yuan (2015)
This report looks into comparison between the various polymeric membrane fabrication methods such as solvent-free heating via electrical heater, reverse heating via portable butane blowtorch, particulate leaching via removing Poly-Ethylene Glycol (PEG) and lastly incorporating particulate leaching with solvent-free heater method. In addition, various surface modification techniques which include non-thermal plasma etching and protein grafting on PCL membrane surface would be employed on Poly-ε-caprolactone (PCL) membranes. Further characterization tests would be employed to determine if the modifications had indeed successfully enhance its mechanical stability, degree of cell moisture permeability, biocompatibility, and lastly cell adhesion and proliferation. Results show that solvent-free fabrication method for PCL and the surface modifications employed were indeed successful in enhancing the cellular viability and moisture permeability.